2017
DOI: 10.1039/c6ra27766g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a core–shell BiVO4@g-C3N4 photo-catalyst with enhanced photocatalytic activity under visible light irradiation

Abstract: Novel core–shell structured ellipsoid-like BiVO4@g-C3N4 composites, with different amounts of g-C3N4, have been successfully prepared by a simple hydrothermal-chemisorption method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…The core‐level spectrum of V 2p displays two peaks at 515.93 and 523.3 eV, which are corresponding to V 2p 3/2 and V 2p 1/2 of V 5+ species of BiVO 4 , respectively (Figure (C)). Three peaks can be detected in the O 1s region (Figure (D)); the main peak at 528.98 eV is corresponding to the lattice oxygen present in the structure of BiVO 4 , while the peaks at 530.18 and 531.58 eV are attributing to the hydroxyl groups and absorbed water molecules on the surface of the sample . The XPS results revealed the successful formation of the g‐C 3 N 4 ‐BiVO 4 nanohybrid material.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The core‐level spectrum of V 2p displays two peaks at 515.93 and 523.3 eV, which are corresponding to V 2p 3/2 and V 2p 1/2 of V 5+ species of BiVO 4 , respectively (Figure (C)). Three peaks can be detected in the O 1s region (Figure (D)); the main peak at 528.98 eV is corresponding to the lattice oxygen present in the structure of BiVO 4 , while the peaks at 530.18 and 531.58 eV are attributing to the hydroxyl groups and absorbed water molecules on the surface of the sample . The XPS results revealed the successful formation of the g‐C 3 N 4 ‐BiVO 4 nanohybrid material.…”
Section: Resultsmentioning
confidence: 93%
“…Electrochemical impedance spectroscopy (EIS) analysis of g‐C 3 N 4 , BiVO 4 and g‐C 3 N 4 ‐BiVO 4 were performed under light illumination to investigate the charge transfer resistance and assess the separation efficiency of photogenerated charge carriers. In the Nyquist plot of EIS, the high‐semicircle radius is assigned to the charge‐transfer limiting process and smaller semicircle radius indicate a smaller electron transfer resistance, which would enhance the electron transfer in the PEC water splitting . It can be observed that BiVO 4 and g‐C 3 N 4 possess large semicircle when compared to the g‐C 3 N 4 ‐BiVO 4 (Figure (C)).…”
Section: Resultsmentioning
confidence: 94%
“…It is clearly observed that the photocurrent of all the samples reaches a constant value as soon as the light is turned on, while decrease to the baseline when the light is off, exhibiting an excellent reproducibility of all the samples. Obviously, B1CN3 delivers the most photocurrent compared with both pure g‐C 3 N 4 nanosheets and pure BiVO 4 nanoplates, indicating a lower recombination and more efficient electron‐hole pairs separation which could be attributed to the formation of Z‐scheme heterojunction between g‐C 3 N 4 nanosheets and BiVO 4 nanoplates …”
Section: Resultsmentioning
confidence: 99%
“…Obviously, B1CN3 delivers the most photocurrent compared with both pure g-C 3 N 4 nanosheets and pure BiVO 4 nanoplates, indicating a lower recombination and more efficient electron-hole pairs separation which could be attributed to the formation of Z-scheme heterojunction between g-C 3 N 4 nanosheets and BiVO 4 nanoplates. 42 In addition, the electrochemical impedance (EIS) is also an effective method to explore the difference among g-C 3 N 4 , BiVO 4 , and BiVO 4 /g-C 3 N 4 in photo-generated electron transfer and charge separation efficiency, which is a critical factor for photocatalytic degradation. It is generally assumed that a smaller arc radius in the Nyquist diagram of EIS represents smaller charge transfer resistance and a faster charge transfer rate.…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%
“…Briefly, a K 3 [Fe(CN) 6 ] aqueous solution (90 mL, 0.05 M) was added dropwise (1 mL/min) to a mixture of excess solutions of Co 2 + (150 mL, 0.05 M) and Mn 2 + (150 mL, 0.05 M) sulfates. The adventitious carbon 1 s signal at 284.8 eV was used as reference for the charge correction for the whole spectrum [29,30] Energy dispersive X-ray fluorescence spectrum (EDXRF) was recorded with a S2 Ranger equipment from Bruker. It is worth noting that the excess of the mixed metals solution relative to the complex anion guarantees that only one phase is formed.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%